2015
DOI: 10.1039/c5dt02005k
|View full text |Cite
|
Sign up to set email alerts
|

Salts of highly fluorinated weakly coordinating anions as versatile precursors towards hydrogen storage materials

Abstract: We report the most recent results related to application of a metathetic pathway towards mixed-metal borohydrides. The synthetic protocol utilizes highly-fluorinated weakly coordinating anion salts as precursors. We discuss the technicalities related to the use of fluorine-rich anions as well as the improvements which are still needed to deliver high-purity materials with potential applications for hydrogen storage. The applicability of the method is expanded beyond the previously described complex borohydride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…While only traces of Li[Al(OR F )4] dissolve in CH2Cl2 it is still sufficient for performing ion metathesis reactions in this solvent. [18][19][20][21][22] The ease of solvation of the relatively soft Ag + cations (that form bonds of much more covalent character than Na or Li) by dichloromethane molecules renders Ag[Al(OR F )4] very well soluble in this solvent. Though without quantitative determination, we have observed that many solvent-free M[Al(OR F )4] salts, particularly with M = Li -K, NH4, N2H5 and Ag, are well soluble in SO2, what broadens the scope of weakly basic and robust solvents usable with these compounds.…”
Section: Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…While only traces of Li[Al(OR F )4] dissolve in CH2Cl2 it is still sufficient for performing ion metathesis reactions in this solvent. [18][19][20][21][22] The ease of solvation of the relatively soft Ag + cations (that form bonds of much more covalent character than Na or Li) by dichloromethane molecules renders Ag[Al(OR F )4] very well soluble in this solvent. Though without quantitative determination, we have observed that many solvent-free M[Al(OR F )4] salts, particularly with M = Li -K, NH4, N2H5 and Ag, are well soluble in SO2, what broadens the scope of weakly basic and robust solvents usable with these compounds.…”
Section: Solubilitymentioning
confidence: 99%
“…8,9 Some of these have shown good or unexpected catalytic activity, [10][11][12][13][14] the others can be potentially useful as electrolytes for batteries [15][16][17] or as convenient synthons towards materials like borohydrides, derivatives of ammonia borane or highly oxidizing compounds. [18][19][20][21][22] Recently, significant advancements in the field of syntheses of two important types of WCAfluorinated arylborates ([B(Ar F )4] -, Ar F = C6H3-3,5-(CF3)2) 23 and the parent carborane [CB11H12] -24 were published in this journal. Along these lines we focus here on the most important WCA representative of the (per)fluorinated alkoxyaluminates, namely [Al{OC(CF3)3}4] − (further denoted as [Al(OR F )4] − ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] This has been manifested in significant growth of the number of known solvent‐free borohydrides, strongly supported by the development of the synthetic methods, in parallel with the structural identification of the products. [ 4–11 ] Besides the storage of hydrogen and their traditional use in reduction processes, borohydrides are studied in the context of solid‐state ion conduction, [ 12–15 ] magnetic and luminescent properties, [ 16–19 ] or as porous materials, capable for loading of guest molecules. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…3 Amongst three new compounds synthesized, 2 and 3 exhibit satisfactory solubility in weakly coordinating organic solvents and they could be utilized as convenient precursors towards various inorganic scandium borohydrides (according to a recently reported metathetic method of synthesis of mixed-metal borohydrides [14,15]). These reactions are now carried out in our laboratory and will be reported elsewhere [16]. …”
Section: Resultsmentioning
confidence: 99%
“…Here the final product is precipitated in a solvent-mediated metathesis reaction between a salt of weakly-coordinating anion, This process has been successfully tested for zinc-and yttrium-based borohydrides for M=Li-K, and Li-Cs, respectively, and dichloromethane (DCM) used as a solvent [14,15,16].…”
Section: Introductionmentioning
confidence: 99%